Autoantigen-harboring apoptotic cells hijack the coinhibitory pathway of T cell activation - Yakoub, Abraam; Seiffert, Martina (Scientific reports, 2018)
Apoptosis is an important physiological process in development and disease. Apoptotic cells (ACs) are a major source of self-antigens, but ACs usually evade immune responses. The mechanism by which ACs repress T cell adaptive immune responses is poorly understood. T cell activation is finely regulated by a balance of costimulatory signaling (mediated by the costimulatory receptor CD28 on T cells) and coinhibitory signaling (mediated by the coinhibitory ligands CD80 and PD-L1 and -2 on Antigen-Presenting Cells). Here, we found that ACs specifically upregulated the coinhibitory ligand CD80 on macrophages. Conversely, ACs did not exhibit a robust regulation of the other coinhibitory ligands on macrophages or the costimulatory receptor CD28 on T cells. We show that the robust positive regulation of CD80 by ACs requires phagocytosis of ACs by macrophages. We also demonstrate that CD80 modulation by dead cells is a specific effect of ACs, but not necrotic cells (which stimulate immune responses). These results indicate that ACs modulate the coinhibitory pathway of T cell activation via CD80, and suggest a role for CD80 in suppressing T cell responses by ACs. Understanding a mechanism of regulating adaptive immune responses to ACs, which harbor an abundance of self-antigens, may advance our understanding of mechanisms of regulating autoimmunity and facilitate future therapy development for autoimmune disorders.
Gesehen am 22.04.2020